2018
DOI: 10.1016/j.jvolgeores.2017.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic crustal deformation by magmatic intrusion: A case study in the Kutcharo caldera, eastern Hokkaido, Japan

Abstract: The linear Maxwell viscoelastic response to the inflation of a sill is examined. • Inflation-induced surface uplift is reduced by viscoelastic relaxation. • Subsidence occurs after magmatic inflation stops. • The subsidence in the Kutcharo caldera is explained by viscoelastic relaxation. • A crustal viscosity of ~4 × 10 17 Pa s is estimated beneath the caldera.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 113 publications
(130 reference statements)
0
23
0
1
Order By: Relevance
“…Newman et al 2001;Del Negro et al 2009;Nooner and Chadwick 2009;Parks et al 2014;Segall 2016;Yamasaki et al 2017).…”
Section: Viscoelastic Relaxationmentioning
confidence: 99%
See 1 more Smart Citation
“…Newman et al 2001;Del Negro et al 2009;Nooner and Chadwick 2009;Parks et al 2014;Segall 2016;Yamasaki et al 2017).…”
Section: Viscoelastic Relaxationmentioning
confidence: 99%
“…In one class of viscoelastic models, the magma chamber sits on the boundary between a hot substrate that behaves viscoelastically and a colder upper elastic layer (Nooner and Chadwick 2009;Yamasaki et al 2017). In the instance of an eruption (or other volume change at the source), such a system behaves identically to a model in which the magma chamber is embedded in an elastic half space, i.e.…”
Section: Viscoelastic Relaxationmentioning
confidence: 99%
“…This situation is justified if the fluids intrudes in previously intact rocks without any previous heating. Yamasaki et al () recently demonstrated that postintrusion deflation that has been ubiquitously observed (Aoki et al, ; Bianchi et al, ; Biggs et al, ; Hutchison et al, ) can be explained simply by a relaxation of viscoelastic substrate without further migration of mass after the unrest ceases.…”
Section: Introductionmentioning
confidence: 99%
“…Posteruptive subsidence has also been ubiquitously observed. A variety of mechanisms can explain posteruptive subsidence, such as magma withdraw (Lu et al, ), consolidation of caldera deposits (Grapenthin et al, ), viscoelastic relaxation of the host rock (Hamling et al, ; Yamasaki et al, ), pore pressure drops associated with hydrothermal fluid circulations (Todesco et al, ; Wauthier et al, ), and magma cooling and contraction (Furuya, ; Tallarico, ). Especially, the last three mechanisms listed above have been highlighted by recent studies because they can cause continuous posteruptive subsidence for decades (Chaussard, ; Furuya, ; Wittmann et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation